Proportions of Patients With HIV Retained in Care and Virally Suppressed in New York City and the United States: Higher Than We Thought. (1st March 2015) - Xia, Qiang; Kersanske, Laura S.; Wiewel, Ellen W.; Braunstein, Sarah L.; Shepard, Colin W.; Torian, Lucia V.
Abstract : Background: The purpose of this analysis is to compare 2 newly developed methods (a "likelihood" method and a "weighting" method) with the widely used method (the "include-all" method) to estimate the proportions of HIV-infected persons retained in care and virally suppressed in New York City (NYC). Methods: The NYC HIV registry data were used for the analysis. The include-all method included all patients in the denominator who were diagnosed and/or receiving care in NYC and not known to be dead by December 31, 2012. The likelihood method included patients in the denominator who were likely to reside in NYC in 2012 based on their length of absence from HIV care. The weighting method included patients in the denominator who were residing in NYC in 2012 by weighting each in-care patient based on their probability of receiving HIV care. Results: The include-all method estimated that 114, 926 persons were diagnosed and living with HIV in NYC, 63.7% were retained in care (≥1 care visit in 2012), and 48.9% were virally suppressed (⩽200 copies/mL). The likelihood method and the weighting method produced equivalent estimates with 80, 074 and 80, 509 persons diagnosed and living with HIV in NYC, 91.5% and 91.0% retained in care, and 70.2% and 71.7% virally suppressed, respectively. Conclusions: Using 2 newly developed methods, we were able to report more accurate estimates of the proportions of patients retained in care and virally suppressed. Other local health jurisdictions should consider using these new methods to measure care outcomes and monitor the National HIV/AIDS Strategy. Abstract : Supplemental Digital Content is Available in the Text.